2021
DOI: 10.1002/cepa.1571
|View full text |Cite
|
Sign up to set email alerts
|

Steel based retrofitting interventions for existing masonry walls: a comparative numerical investigation

Abstract: Masonry buildings constitute a significant portion of the architectural heritage all over the world, also in regions affected by a high seismic hazard. Since this constructional material is characterized by lack of tensile strength, as well as small deformation capacity, masonry structures could result hugely damaged if shaken by seismic forces. In order to avoid collapses and reduce structural damage, innovative retrofitting interventions are necessary to improve the seismic behavior of masonry structures. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In the plane of the wall, however, the rectangular arrangement does not bring any increase in strength or stiffness. Both in-depth experimental tests [37] and recent numerical analyses [38], in fact, have shown that the rectangular arrangement of the stainless steel straps leads to an almost negligible increase in the strength of the shear-loaded masonry panels while providing a significant increase in ductility. The use of steel grids on both faces of the masonry wall, conversely, increases both the shear strength and the ductility, but the ultimate displacement achieved with the steel grids is lower than that achieved with the CAM ® system [38].…”
Section: The Idea Behind the Experimental Programmentioning
confidence: 99%
See 3 more Smart Citations
“…In the plane of the wall, however, the rectangular arrangement does not bring any increase in strength or stiffness. Both in-depth experimental tests [37] and recent numerical analyses [38], in fact, have shown that the rectangular arrangement of the stainless steel straps leads to an almost negligible increase in the strength of the shear-loaded masonry panels while providing a significant increase in ductility. The use of steel grids on both faces of the masonry wall, conversely, increases both the shear strength and the ductility, but the ultimate displacement achieved with the steel grids is lower than that achieved with the CAM ® system [38].…”
Section: The Idea Behind the Experimental Programmentioning
confidence: 99%
“…Both in-depth experimental tests [37] and recent numerical analyses [38], in fact, have shown that the rectangular arrangement of the stainless steel straps leads to an almost negligible increase in the strength of the shear-loaded masonry panels while providing a significant increase in ductility. The use of steel grids on both faces of the masonry wall, conversely, increases both the shear strength and the ductility, but the ultimate displacement achieved with the steel grids is lower than that achieved with the CAM ® system [38]. The author of this article is of the opinion that the lack of increase in shear strength with the CAM ® system depends on the arrangement of the perforations, which makes the strengthening system labile to horizontal loads [29].…”
Section: The Idea Behind the Experimental Programmentioning
confidence: 99%
See 2 more Smart Citations